Paper of Dagestan Arabographic Manuscripts and Epistolary Documents of 19th — Early 20th Centuries: Ways of Receipt and Chronology of Use - Z. B. Ibragimova; Z. A. Magomedova (Научный диалог)
The article is devoted to the paper of Dagestan Arabic manuscripts and epistolary documents of the 19th — early 20th centuries, as an important aspect of source study. This work allows you to get an idea of the history of Russia’s cultural and economic ties with Dagestan and the countries of the East. In the course of the study, a comparative historical method was used. The authors analyzed the works of domestic and foreign experts on this issue, highlighted the main identification features of the paper of these written documents. The relevance of the ongoing research is due to the need for a comprehensive study of the writing material of the Arabographic monuments of Dagestan origin. The novelty of the work lies in the fact that the paper of these historical sources for the first time became the object of study in domestic source studies. It has been established that in the Dagestan manuscripts and epistolary documents of the 19th — early 20th centuries, the marked paper of Russian manufactories and factories is mainly represented. The article notes that for a full-fledged study of Dagestan Arabographic sources, it is necessary to use advanced digital technology and modern natural scientific developments. The study of historical sources paper is of great importance in the preservation and restoration of monuments of the written culture of the Dagestan peoples.